Motivational Factors to Learn English among University Students in An Urban Area - Adara, Reza Anggriyashati (Yayasan Sukma, 2019)
Motivation can be considered as one of influential factors in foreign language (FL) learning as it helps to sustain learner’s interest during long and tedious learning process of FL. According to Deci and Ryan (2000), motivation can be categorized into two types; intrinsic and extrinsic motivation. The present study aims to investigate intrinsic and extrinsic motivational factors of a group of university students in an urban area to learn English. The present study applied a mixed method approach by administering a set of questionnaires and interviews. In addition to a relatively high level of motivation among the participants, the findings of present study show an interest in English language skills and positive attitudes to native speakers of English, English speaking countries, and English learning as intrinsic motivational factors to learn English. On the other hand, the chances of getting better jobs and personal development as extrinsic factors which motivate students to learn English. The present study recommends English teachers as well as educational institutions to provide teaching and learning materials which suited to improve students’ motivation.